Notes on the Cultivation of Two Mixotrophic Dinophysis Species and Their Ciliate Prey Mesodinium rubrum - Hernández-Urcera, Jorge (Toxins (Basel), 2018)
Kleptoplastic mixotrophic species of the genus Dinophysis are cultured by feeding with the ciliate Mesodinium rubrum, itself a kleptoplastic mixotroph, that in turn feeds on cryptophytes of the Teleaulax/Plagioselmis/Geminigera (TPG) clade. Optimal culture media for phototrophic growth of D. acuminata and D. acuta from the Galician Rías (northwest Spain) and culture media and cryptophyte prey for M. rubrum from Huelva (southwest Spain) used to feed Dinophysis, were investigated. Phototrophic growth rates and yields were maximal when D. acuminata and D. acuta were grown in ammonia-containing K(-Si) medium versus f/2(-Si) or L1(-Si) media. Dinophysis acuminata cultures were scaled up to 18 L in a photobioreactor. Large differences in cell toxin quota were observed in the same Dinophysis strains under different experimental conditions. Yields and duration of exponential growth were maximal for M. rubrum from Huelva when fed Teleaulax amphioxeia from the same region, versus T. amphioxeia from the Galician Rías or T. minuta and Plagioselmis prolonga. Limitations for mass cultivation of northern Dinophysis strains with southern M. rubrum were overcome using more favorable (1:20) Dinophysis: Mesodinium ratios. These subtleties highlight the ciliate strain-specific response to prey and its importance to mass production of M. rubrum and Dinophysis cultures.